2013
DOI: 10.1007/s00787-013-0444-4
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral problems in school-aged hearing-impaired children: the influence of sociodemographic, linguistic, and medical factors

Abstract: The purpose of this study was to examine several behavioral problems in school-aged hearing-impaired children with hearing aids or cochlear implants, compared to normally hearing children. Additionally, we wanted to investigate which sociodemographic, linguistic, and medical factors contributed to the level of behavioral problems, to pinpoint where targeted interventions can take place. This large, retrospective study included a sample of 261 school-aged children (mean age = 11.8 years, SD = 1.6), that consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
113
0
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(133 citation statements)
references
References 36 publications
12
113
0
8
Order By: Relevance
“…34 However, in DHH children without development delays, behavioral problems have been identified in areas of hyperactivity, aggression, peer interactions, and isolation. 35,36 These behavioral issues often go unrecognized and untreated. Theuniseen et al demonstrated that school-aged DHH children who used either HA or CI were more likely to exhibit behavioral problems and aggression than NH children, based on multiple parent- and self-report instruments.…”
Section: Discussionmentioning
confidence: 99%
“…34 However, in DHH children without development delays, behavioral problems have been identified in areas of hyperactivity, aggression, peer interactions, and isolation. 35,36 These behavioral issues often go unrecognized and untreated. Theuniseen et al demonstrated that school-aged DHH children who used either HA or CI were more likely to exhibit behavioral problems and aggression than NH children, based on multiple parent- and self-report instruments.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, although no difference was found between these two groups in terms of aggressive behaviors until they reach 14 years of age, the increase in the aggressive behaviors of children with hearing impairment after this age is noteworthy. When we reviewed the studies focusing on this topic, although there are some studies suggesting that aggression increases as the age of children increases (Tok, 2001;Theunissen et al, 2014), some other studies suggest that aggression is a behavior that can be seen at every age of the children (Köksal, 1991;Arıcak, 1995;Tuzgöl, 1998;Gümüş, 2000). Children included in the study group are in their adolescence period.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research shows that contemporary children with CI(s) have approximately the same levels of anxiety as normal hearing children and less than children with hearing aids (Barker et al, 2009;Theunissen et al, 2012Theunissen et al, , 2014a. Lower levels of general and social anxiety are attributed to early intervention, and possibly also to more intensive rehabilitation (than children with hearing aids).…”
Section: Demographics and Rehabilitationmentioning
confidence: 99%